Mechanisms of responsibility assignment during redundant reaching movements - Reichenbach, Alexandra (American Physiological Society, 2013)
When the two hands act together to achieve a goal, the redundancy of the system makes it necessary to distribute the responsibility for error corrections across the two hands. In an experiment in which participants control a single cursor with the movements of both hands, we show that right-handed individuals correct for movement errors more with their nondominant left hand than with their right hand, even though the dominant right hand corrects the same errors more quickly and efficiently when each hand acts in isolation. By measuring the responses to rapid cursor and target displacements using force channels, we demonstrate that this shift is due to a modulation of the feedback gains of each hand rather than to a shift in the onset of the corrective response. We also show that the shift toward left-hand corrections is more pronounced for errors that lead to adaptation (cursor displacements) than for perturbations that do not (target displacements). This finding provides some support for the idea that the motor system assigns the correction to the most likely source of the error to induce learning and to optimize future performance. Finally, we find that the relative strength of the feedback corrections in the redundant task correlates positively with those found for the nonredundant tasks. Thus the process of responsibility assignment modulates the processes that normally determine the gains of feedback correction rather than completely overwriting them.